Analisis Potensi Penyerapan Karbon Atmosferik di Stasiun Penelitian Hutan Bron Desa Warembungan Kab. Minahasa - Caroline N.A.C. Tasirin; Martina A. Langi; Hengky D. Walangitan; Josephus I. Kalangi (COCOS, 2013)
ABSTRACTThis study aims to analyze the current carbon stock of Bron Forest Research Station, Warembungan village, regency of Minahasa, and to analyze the potential of Bron Forest Research Station in sequestering atmospheric carbon. This study was done in Bron Forest Research Station, Warembungan village, regency of Minahasa, for three months. Measurements for this study were done in 15 systematically placed observation plots. The measured variables were diameter at breast height, bole height, and the mass of litter and understory.The results of this study shows that Bron Forest Research Station has a total biomass of 49,821.84 tonnes, or 996.44 tonnes/ha. This biomass consists of 23,416.27 tonnes of carbon, atau 468.33 tonnes/ha. Up to the time of the study, Bron Forest Research Station has sequestered 85,859.65 tonnes of carbon dioxide from the atmosphere, or 1,717.19 tonnes/ha. Assuming the forest does not undergo any significant change, Bron Forest Research Station will potentially increase its biomass as by 4.66 tonnes/ha/year, or 232.90 tonnes/year for the entire 50-hectares area. This additional biomass entails an increase of carbon stock by 1.72 tonnes/ha/year, or as much as 86.17 tonnes/year for the whole area. Bron Forest Research Station will potentially sequester an additional 6.32 tonnes/ha/year of carbon dioxide from the atmosphere, or as much as 315.97 tonnes/year for the whole area.Keywords: biomass, carbon sequestration, carbon dioxide sequestration.